HLA variation associated with peanut allergy and anaphylaxis among non-Hispanic Black individuals - Baojun Wu, PhD; Mao Yang, MS; Donglei Hu, PhD; Ray Zhang; Bin Liu, PhD, MPH; Samantha Hochstadt, MS; David E. Lanfear, MD, MS; Jonathan Witonsky, MD, MAS; Rajesh Kumar, MD, MS; Jill A. Hollenbach, PhD, MPH; Esteban G. Burchard, MD, MPH; Elad Ziv, MD; et al. (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Peanut is a major cause of food allergy. HLA genes have been consistently associated with peanut allergy in association studies. To date, however, there have been very few genetic studies of peanut allergy in non-Hispanic Black (Black) individuals, a group disproportionately affected by food allergy. Objective: Our aim was to study the relationship between HLA alleles and peanut allergy among Black individuals. Methods: The analysis consisted of Black participants from the Study of Asthma-Related Phenotypes and Pharmacogenomic Interactions by Race-Ethnicity (SAPPHIRE), a large cohort of individuals from metropolitan Detroit. At the time of enrollment, participants provided detailed food allergy histories, including symptoms. Four-digit resolution HLA allele calls were made using whole genome sequence data. Results: The cases consisted of 119 individuals with reported peanut allergy and 59 individuals with peanut-related anaphylaxis; the comparison group consisted of 2640 individuals without reported food allergy. HLA-DRB1∗13:02 was the most significant allele associated with peanut allergy (adjusted odds ratio = 1.94 [95% CI = 1.28-2.93]), and HLA-DQA1∗01:02 was the top association with peanut-related anaphylaxis (aOR = 1.67 [95% CI = 1.14-2.44]). Amino acid polymorphisms at position 71 in the binding groove of HLA-DRB1 were associated with peanut allergy and estimated to affect peanut allergen binding affinity. Conclusions: In a cohort of Black individuals, this study independently identified the same associations of peanut allergy and HLA that were previously observed in non-Hispanic White individuals. Our findings suggest that specific HLA binding groove amino acid polymorphisms may confer similar peanut allergy risk across population groups and HLA alleles.